Greenhouse film

By optimizing the components and dosage of each layer of the greenhouse film, designing dust-proof and aging-resistant layer, thermal insulation and aging-resistant layer and coating liquid bearing layer, the problem of short dust-proof function of the existing greenhouse film is solved and long-term dust-proof protection is achieved and the improvement of thermal insulation performance, suitable for high-end facility agriculture.

CN119502511APending Publication Date: 2025-02-25LUCKY FILM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411641674.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The dustproof function of the existing greenhouse greenhouse film has a short age, which affects its service life and limits its application in high-end facility agricultural scenarios.

Method used

By optimizing the components and dosages of each layer of the shed film, the composition of the outer layer, the core layer and the inner layer are designed. The outer layer is a dust-proof and aging-resistant layer, the core layer is a thermal insulation and aging-resistant layer, and the inner layer is a coating liquid bearing layer. Polar resin is added to each layer, especially ethylene-vinyl acetate copolymer is added to the core layer to improve thermal insulation performance and polar compatibility.

Benefits of technology

It realizes the long-term dust-proof function of the shed film, extends the service life, and improves the insulation performance, and is suitable for high-end facility agricultural scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005138631810000151
    Figure BDA0005138631810000151
  • Figure BDA0005138631810000161
    Figure BDA0005138631810000161
  • Figure BDA0005138631810000162
    Figure BDA0005138631810000162
Patent Text Reader

Abstract

The invention discloses a greenhouse film which comprises an outer layer, an inner layer and a core layer located between the outer layer and the inner layer. The outer layer is prepared from the following components in parts by mass: 40 to 60 parts of polyethylene I, 10 to 20 parts of polar resin I, 10 to 20 parts of polar resin II, 5 to 15 parts of dust-proof agent, 5 to 20 parts of anti-aging master batch and 1 to 7 parts of ultraviolet absorption master batch, wherein the mass part of the polyethylene I is (100): 40 to 60 parts of polyethylene I, 10 to 20 parts of polar resin I, 10 to 20 parts of polar resin II, 5 to 15 parts of dust-proof agent, 5 to 20 parts of anti-aging master batch and 1 to 7 parts of ultraviolet absorption master batch. In addition, the core layer comprises polyethylene I, polar resin II, heat preservation master batch and anti-aging master batch. And the inner layer comprises the following components: polyethylene I, polar resin I, polar resin II and an anti-aging master batch. The polar resin I comprises an ethylene-methacrylic acid copolymer; the polar resin II comprises an ethylene-vinyl acetate copolymer; the dustproof agent comprises a high-molecular permanent antistatic agent. According to the greenhouse film provided by the invention, the conditions are met by optimizing the raw material components and the dosage of each layer, so that the long-acting dustproof function is favorably realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of agricultural films, and in particular to greenhouse films. Background Art

[0002] With the continuous development of facility agriculture, the requirements for agricultural greenhouse films have been further improved, and the greenhouse film market is gradually developing towards high-end areas. The greenhouse films currently on the market generally have the problem of short dust-proof function and affect the service life of the greenhouse films, which limits their application in some high-end facility agriculture scenarios. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to provide a greenhouse film, and the greenhouse film of the present application is conducive to achieving a long-term dustproof function of the greenhouse film by optimizing the components and dosage of each layer.

[0004] The first aspect of the present application provides a greenhouse film. According to an embodiment of the present application, the greenhouse film includes: an outer layer and an inner layer, and a core layer located between the outer layer and the inner layer;

[0005] The components of the outer layer include:

[0006] Polyethylene I, 40 to 60 parts,

[0007] Polar resin I, 10 to 20 parts,

[0008] Polar resin II, 10 to 20 parts,

[0009] Dust suppressant, 5 to 15 parts,

[0010] Anti-aging masterbatch, 5 to 20 parts,

[0011] UV absorbing masterbatch, 1 to 7 parts;

[0012] The components of the core layer include:

[0013] Polyethylene I, 40 to 60 parts,

[0014] Polar resin II, 20 to 40 parts,

[0015] Insulation masterbatch, 1 to 6 parts,

[0016] Anti-aging masterbatch, 5 to 20 parts;

[0017] The components of the inner layer include:

[0018] Polyethylene I, 50 to 70 parts,

[0019] Polar resin I, 10 to 20 parts,

[0020] Polar resin II, 10 to 20 parts,

[0021] Anti-aging masterbatch, 0 to 15 parts;

[0022] Polar resin I includes ethylene-methacrylic acid copolymer;

[0023] Polar resin II includes ethylene-vinyl acetate copolymer;

[0024] Dust suppressants include polymer permanent antistatic agents.

[0025] The greenhouse film provided by the present application has an outer layer as a dustproof and aging-resistant layer, a core layer as a heat-insulating and aging-resistant layer, and an inner layer as a coating liquid bearing layer. The raw material components and dosages of each layer meet the above conditions, which is conducive to achieving a long-term dustproof function.

[0026] Polar resins are added to each layer of the present application. The polar resin added to the core layer is ethylene-vinyl acetate copolymer (EVA for short). The introduction of polar groups can effectively improve the compatibility of the resin system with anti-aging additives, increase the amount of additives added, and further extend the service life of the greenhouse film. In addition, EVA has a strong infrared absorption capacity, which can improve the thermal insulation performance of the greenhouse film. In the core layer, the amount of EVA is controlled at 20% to 40%. When the amount is less than 20%, the polarity of the overall formula is limited. When the amount of additives required for anti-aging is added, there will be migration; when the amount is higher than 40%, first, it will lead to a decrease in the overall tensile strength of the core layer, and it is easy to break the greenhouse in the later use. Second, the price of EVA is higher than that of polyethylene, which will cause an increase in costs. Therefore, it is reasonable to control the amount at 20% to 40%. The dosage of the two surface layers of EVA is controlled at 10% to 20%. When the dosage is lower than 10%, not only is the polarity of the overall formula limited, but it also cannot be used as a compatibilizer to adjust the compatibility between EMA and polyethylene I, which can easily cause orange peel texture. When the dosage is higher than 20%, firstly, it will lead to a decrease in the overall tensile strength of the core layer, and it is easy to break in the later use. Second, the price of EVA is higher than that of polyethylene, which will cause an increase in cost. Therefore, it is reasonable to control the dosage at 10% to 20%.

[0027] The present application adds ethylene-methacrylic acid copolymer (EMA) to two surfaces (i.e., the outer layer and the inner layer). EMA resin has a higher polarity than EVA and good hydrolysis resistance. It can be used in the outer layer to increase the polarity of the layer, achieve compatibility with the polymer permanent antistatic agent, and avoid the problems of apparent flower blooming, molding difficulties, and antistatic agent flower blooming caused by the incompatibility of the polymer permanent antistatic agent with the matrix resin. In addition, the compatibility of the auxiliary agent can be improved to ensure the weather resistance of the outer layer. It can be used in the inner layer to improve the surface energy and achieve better adhesion performance with the dripping defogging coating liquid. In the outer layer, the amount of EMA is controlled at 10% to 20%, and in the inner layer, the amount of EMA is controlled at 10% to 20%. When the amount is less than 10%, not only the polarity of the overall formula is limited, but also it cannot be well matched with the auxiliary agent and the coating liquid; when the amount is higher than 20%, because the EMA bonding performance is strong, it will cause the surface layer to be sticky, which is not conducive to production and the opening of the later film. Therefore, it is reasonable to control the dosage within 10% to 20%. In addition, due to the incompatibility between EMA and polypropylene, the film making process is prone to problems such as "orange peel" on the surface, so a certain amount of EVA is still added to the system to play a role in increasing the capacity.

[0028] The present application adds a polymer permanent antistatic agent as a dustproof agent in the outer layer. The polymer permanent antistatic agent is a hydrophilic polymer. When it is blended with the polyethylene matrix, on the one hand, the molecular chain has a strong mobility, and the molecules are easy to move protons, and the generated static charge can be conducted and released through ion conduction; on the other hand, it is distributed in fine layers or tendons on the surface of the product to form a conductive surface, and in the center it is almost spherical, forming a so-called "core-shell structure", and uses this as a path to leak static charge. The polymer permanent antistatic agent can reduce the volume resistivity of the material to achieve an antistatic effect, has permanent non-migration, and can achieve permanent antistatic and dustproof effects. The dosage of the outer layer polymer permanent antistatic agent is controlled at 5% to 15%. When the dosage is less than 5%, it cannot form a continuous layered or ribbed distribution on the surface of the film, and cannot form a connected "core-shell structure". The charge cannot be smoothly discharged, affecting the antistatic effect; when the dosage is higher than 15%, firstly, the excessive introduction of high-molecular materials that are out of phase with the main body will bring compatibility problems, and secondly, the price of polymer permanent antistatic agents is relatively expensive, which will cause the cost to rise. Therefore, it is reasonable to control the dosage at 5% to 15%.

[0029] According to an embodiment of the present application, the content of methacrylic acid in the ethylene-methacrylic acid copolymer is 12% to 29%; and / or the content of vinyl acetate in the ethylene-vinyl acetate copolymer is 8% to 18%.

[0030] According to an embodiment of the present application, the melting point of the dust suppressant is less than 150° C., and / or the viscosity of the dust suppressant is greater than the viscosity of the mixture of polyethylene I, polar resin I and polar resin II.

[0031] According to the embodiments of the present application, the melt index of polyethylene I is 0.2 g / 10 min to 1.0 g / 10 min.

[0032] According to the embodiments of the present application, based on 100 parts by mass, the components of the aging-resistant masterbatch include:

[0033] Polyethylene II, 40 to 60 parts,

[0034] Light stabilizer, 30 to 50 parts,

[0035] Antioxidant, 0.5 to 5 parts;

[0036] And / or, based on 100 parts by mass, the components of the ultraviolet absorbing masterbatch include:

[0037] Polyethylene II, 70 to 90 parts,

[0038] Ultraviolet absorber, 10 to 30 parts.

[0039] According to an embodiment of the present application, polyethylene II includes low-density polyethylene, and the melt index of polyethylene II is ≥2.0 g / 10 min.

[0040] According to an embodiment of the present application, the greenhouse film satisfies at least one of the following:

[0041] In the anti-aging masterbatch, the light stabilizer includes a hindered amine light stabilizer;

[0042] In the anti-aging masterbatch, the antioxidant includes a composite type of hindered phenols and phosphites;

[0043] In the ultraviolet absorbing masterbatch, the ultraviolet absorber includes at least one of a salicylate ultraviolet absorber, a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber, a hindered amine ultraviolet absorber, a substituted acrylonitrile ultraviolet absorber and a triazine ultraviolet absorber.

[0044] According to an embodiment of the present application, the thermal insulation masterbatch includes hydrotalcite masterbatch.

[0045] According to an embodiment of the present application, the greenhouse film further includes a coating layer, and the coating layer covers the surface of the inner layer.

[0046] According to an embodiment of the present application, the thickness ratio of the outer layer, the core layer and the inner layer is (1-2):(3-8):1, and / or the total thickness of the greenhouse film is 130 μm to 170 μm.

[0047] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION

[0048] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0049] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0050] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.

[0051] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0052] With the continuous development of facility agriculture, the requirements for agricultural greenhouse films have been further improved, and the greenhouse film market is gradually developing towards high-end areas. The greenhouse films currently on the market generally have the problem of short dust-proof function and affect the service life of the greenhouse films, which limits their application in some high-end facility agriculture scenarios.

[0053] Polymer permanent antistatic agents have been used in other industries, but they have poor compatibility with the base resin, which results in reduced antistatic effect, affects appearance and molding, and affects durability, limiting their application in the greenhouse film field.

[0054] To this end, a first aspect of an embodiment of the present application provides a greenhouse film, comprising: an outer layer and an inner layer, and a core layer located between the outer layer and the inner layer;

[0055] The components of the outer layer include:

[0056] Polyethylene I, 40 to 60 parts,

[0057] Polar resin I, 10 to 20 parts,

[0058] Polar resin II, 10 to 20 parts,

[0059] Dust suppressant, 5 to 15 parts,

[0060] Anti-aging masterbatch, 5 to 20 parts,

[0061] UV absorbing masterbatch, 1 to 7 parts;

[0062] The components of the core layer include:

[0063] Polyethylene I, 40 to 60 parts,

[0064] Polar resin II, 20 to 40 parts,

[0065] Insulation masterbatch, 1 to 6 parts,

[0066] Anti-aging masterbatch, 5 to 20 parts;

[0067] The components of the inner layer include:

[0068] Polyethylene I, 50 to 70 parts,

[0069] Polar resin I, 10 to 20 parts,

[0070] Polar resin II, 10 to 20 parts,

[0071] Anti-aging masterbatch, 0 to 15 parts.

[0072] Polar resin I includes ethylene-methacrylic acid copolymer;

[0073] Polar resin II includes ethylene-vinyl acetate copolymer;

[0074] Dust suppressants include polymer permanent antistatic agents.

[0075] The greenhouse film provided in the embodiment of the present application has an outer layer as a dustproof and aging-resistant layer, a core layer as a heat-insulating and aging-resistant layer, and an inner layer as a coating liquid bearing layer. The raw material components and dosages of each layer meet the above conditions, which is conducive to achieving a long-term dustproof function.

[0076] In the examples of the present application, polar resin is added to each layer.

[0077] The polar resin added to the core layer is ethylene-vinyl acetate copolymer (EVA for short). The introduction of polar groups can effectively improve the compatibility of the resin system with anti-aging additives, increase the amount of additives added, and further extend the service life of the greenhouse film. In addition, EVA has a strong infrared absorption capacity, which can improve the thermal insulation performance of the greenhouse film. In the core layer, the amount of EVA is controlled at 20% to 40%. When the amount is less than 20%, the polarity of the overall formula is limited. When the amount of additives required for anti-aging is added, there will be migration. When the amount is higher than 40%, first, it will lead to a decrease in the overall tensile strength of the core layer, and it is easy to break the greenhouse in the later use. Second, the price of EVA is higher than that of polyethylene, which will cause an increase in costs. Therefore, it is reasonable to control the amount at 20% to 40%. The dosage of the two surface layers of EVA is controlled at 10% to 20%. When the dosage is lower than 10%, not only is the polarity of the overall formula limited, but it also cannot be used as a compatibilizer to adjust the compatibility between EMA and polyethylene I, which can easily cause orange peel texture. When the dosage is higher than 20%, firstly, it will lead to a decrease in the overall tensile strength of the core layer, and it is easy to break in the later use. Second, the price of EVA is higher than that of polyethylene, which will cause an increase in cost. Therefore, it is reasonable to control the dosage at 10% to 20%.

[0078] In the embodiment of the present application, ethylene-methacrylic acid copolymer (EMA) is added to two surfaces (i.e., the outer layer and the inner layer). EMA resin has higher polarity than EVA and good hydrolysis resistance. It can be used in the outer layer to increase the polarity of the layer, achieve compatibility with the polymer permanent antistatic agent, and avoid the problems of apparent flower blooming, molding difficulties, and antistatic agent flower blooming caused by the incompatibility of the polymer permanent antistatic agent with the matrix resin. In addition, the compatibility of the auxiliary agent can be improved to ensure the weather resistance of the outer layer. It can be used in the inner layer to improve the surface energy and achieve better adhesion performance with the dripping defogging coating liquid. In the outer layer, the amount of EMA is controlled at 10% to 20%, and in the inner layer, the amount of EMA is controlled at 10% to 20%. When the amount is less than 10%, not only the polarity of the overall formula is limited, but also it cannot be well matched with the auxiliary agent and the coating liquid; when the amount is higher than 20%, because the EMA bonding performance is strong, it will cause the surface layer to be sticky, which is not conducive to production and the opening of the later film. Therefore, it is reasonable to control the dosage within 10% to 20%. In addition, due to the incompatibility between EMA and polypropylene, the film making process is prone to problems such as "orange peel" on the surface, so a certain amount of EVA is still added to the system to play a role in increasing the capacity.

[0079] In a specific example, in the outer layer, the amount of polar resin I added is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc. The amount of polar resin II added is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.

[0080] In specific examples, in the core layer, the amount of polar resin II added is 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, etc.

[0081] In a specific example, in the inner layer, the amount of polar resin I added is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc. The amount of polar resin II added is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.

[0082] In the embodiment of the present application, a polymer permanent antistatic agent is added to the outer layer as a dustproof agent. The polymer permanent antistatic agent is a hydrophilic polymer. When it is blended with the polyethylene matrix, on the one hand, the molecular chain has a strong mobility, and the molecules are easy to move protons, and the generated static charge can be conducted and released through ion conduction; on the other hand, it is distributed in a fine layer or tendon shape on the surface of the product to form a conductive surface layer, and in the center part it is almost spherical, forming a so-called "core-shell structure", and using this as a path to leak static charge. The polymer permanent antistatic agent can reduce the volume resistivity of the material to achieve an antistatic effect, has permanent non-migration, and can achieve permanent antistatic and dustproof effects.

[0083] The dosage of the outer layer polymer permanent antistatic agent is controlled at 5% to 15%. When the dosage is less than 5%, it cannot form a continuous layered or ribbed distribution on the surface of the film, and cannot form a connected "core-shell structure". The charge cannot be smoothly discharged, affecting the antistatic effect; when the dosage is higher than 15%, firstly, the excessive introduction of high-molecular materials that are out of phase with the main body will bring compatibility problems, and secondly, the price of polymer permanent antistatic agents is relatively expensive, which will cause the cost to rise. Therefore, it is reasonable to control the dosage at 5% to 15%.

[0084] In specific examples, the amount of dust suppressant added is 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc.

[0085] In some embodiments of the present application, the raw material composition of the greenhouse film is:

[0086] The components of the outer layer include:

[0087] Polyethylene I, 44 to 50 parts,

[0088] Polar resin I, 13 to 18 parts,

[0089] Polar resin II, 13 to 18 parts,

[0090] Dust suppressant, 8 to 12 parts,

[0091] Anti-aging masterbatch, 8 to 18 parts,

[0092] UV absorbing masterbatch, 2 to 5 parts;

[0093] The components of the core layer include:

[0094] Polyethylene I, 44 to 55 parts,

[0095] Polar resin II, 23 to 35 parts,

[0096] Thermal insulation masterbatch, 2 to 5 parts,

[0097] Aging-resistant masterbatch, 8 to 12 parts;

[0098] The components of the inner layer include:

[0099] Polyethylene I, 55 to 65 parts,

[0100] Polar resin I, 12 to 18 parts,

[0101] Polar resin II, 12 to 18 parts,

[0102] Anti-aging masterbatch, 5 to 10 parts.

[0103] In some embodiments of the present application, the content of methacrylic acid in the ethylene-methacrylic acid copolymer is 12% to 29%; and / or the content of vinyl acetate in the ethylene-vinyl acetate copolymer is 8% to 18%.

[0104] In the embodiment of the present application, the content of vinyl acetate (VA) in the ethylene-vinyl acetate copolymer is 8% to 18%, so that the greenhouse film has excellent flexibility, impact resistance, elasticity, and optical transparency.

[0105] In the embodiments of the present application, the content of methacrylic acid (MA) in the ethylene-methacrylic acid copolymer is 12% to 29%. If the MA content is too low, the polarity of the material will be low, and it will be difficult to ensure compatibility with polymer permanent antistatic agents and anti-aging additives. However, too high a MA content will affect the fluidity and plasticity of the material, thereby affecting the formability during processing and the final appearance of the product. In specific examples, the content of methacrylic acid is 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, etc.

[0106] In some embodiments of the present application, the ethylene-vinyl acetate copolymer includes at least one of FL00014 produced by ExxonMobil, FL00018 produced by ExxonMobil, V4110F produced by BASF-YPC, E120A produced by Hanwha, and 14-2 produced by Beijing Organic Chemical.

[0107] In some embodiments of the present application, the ethylene-methacrylic acid copolymer includes at least one of the 24MA005 and 18MA03 grades produced by Arkema of France.

[0108] In some embodiments of the present application, the melting point of the dust suppressant is less than 150° C., and / or the viscosity of the dust suppressant is greater than the viscosity of the mixture of polyethylene I, polar resin I and polar resin II.

[0109] In the embodiments of the present application, the dispersion degree and state of the antistatic agent determine the antistatic effect.

[0110] In the embodiments of the present application, a polyamide polyether type polymer antistatic agent with a melting point of less than 150°C is specifically used. This type of antistatic agent has little effect on the performance of the base material and can achieve good compatibility with polyethylene at the processing temperature of polyethylene when used in combination with a polar resin.

[0111] In the embodiment of the present application, the viscosity of the polymer permanent antistatic agent is controlled to be greater than the viscosity of the mixture of the polyethylene, polar resin I and polar resin II used. The difference in viscosity can make it easier for the low-viscosity base resin to form a continuous phase and be easily coated on the surface of the antistatic agent with higher viscosity. In addition, by controlling the viscosity, a small amount of antistatic agent can also be present as a continuous dispersed phase in a large amount of base resin, distributed in a network and fixed during the molding process, which can enhance the antistatic effect.

[0112] Furthermore, the polymer permanent antistatic agent includes a polyamide polyether polymer antistatic agent.

[0113] Furthermore, the polymer permanent antistatic agent includes the antistatic agent produced by Sanyo Chemical or the antistatic agent produced by Croda.

[0114] In some embodiments of the present application, the melt index of polyethylene I is 0.2g / 10min to 1.0g / 10min. In specific examples, the melt index of polyethylene I is 0.2g / 10min, 0.3g / 10min, 0.4g / 10min, 0.5g / 10min, 0.6g / 10min, 0.7g / 10min, 0.8g / 10min, 0.9g / 10min, 1g / 10min, etc.

[0115] Furthermore, polyethylene I is metallocene linear low-density polyethylene (mLLDPE), and the melt index of the metallocene polyethylene is less than 1.0 g / 10 min.

[0116] In the embodiments of the present application, the metallocene linear low-density polyethylene (metallocene LLDPE) has a higher relative molecular mass and a denser molecular distribution, which enables it to better resist breakage and impact when subjected to external forces and maintain the integrity and functionality of the material. The transparency of the polyethylene polymer will increase with the increase of molecular weight. When the crystallinity is certain, the transparency of the metallocene LLDPE is better than that of traditional polyethylene, which improves the light transmittance, strength and rubbing resistance of the greenhouse film, and effectively prevents the "backboard effect" of the greenhouse film.

[0117] Furthermore, the metallocene linear low-density polyethylene includes at least one of 2010MA, 2005MC, XP6056 ML, and XP6026 ML grades produced by ExxonMobil.

[0118] In some embodiments of the present application,

[0119] Based on 100 parts by mass, the components of the aging-resistant masterbatch include:

[0120] Polyethylene II, 40 to 60 parts,

[0121] Light stabilizer, 30 to 50 parts,

[0122] Antioxidant, 0.5 to 5 parts;

[0123] And / or, based on 100 parts by mass, the components of the ultraviolet absorbing masterbatch include:

[0124] Polyethylene II, 70 to 90 parts,

[0125] Ultraviolet absorber, 10 to 30 parts.

[0126] In the embodiment of the present application, anti-aging masterbatch is added to the outer layer, core layer and inner layer. The components and content of the anti-aging masterbatch meet the above conditions, which is beneficial to improving the overall anti-aging performance of the greenhouse film.

[0127] In this embodiment, a UV absorbing masterbatch is added to the outer layer. The components and content of the UV absorbing masterbatch meet the above conditions, which is conducive to improving the radiation resistance and aging resistance of the greenhouse film. Ultraviolet rays are the root cause of the degradation of greenhouse films. Ultraviolet rays can be eliminated or partially eliminated by ultraviolet absorbers. Furthermore, several ultraviolet absorbers with different central absorption wavelengths can be used in combination to better control the cutoff of ultraviolet light of the product.

[0128] In some embodiments of the present application, polyethylene II includes low-density polyethylene, and the melt index of polyethylene II is greater than 2.0 g / 10 min.

[0129] Furthermore, the melt index of polyethylene II is 2.0g / 10min to 4.0g / 10min. When the melt index is greater than 2.0g / 10min, the polyethylene has good fluidity, making the molding process more convenient during the preparation of the anti-aging masterbatch or the ultraviolet absorption masterbatch. However, if the melt index is too high, the fluidity of the anti-aging masterbatch or the ultraviolet absorption masterbatch will be greatly different from that of the greenhouse film base material, and there will be a fluidity mismatch problem during the film making process, resulting in poor film appearance.

[0130] In some embodiments of the present application, at least one of the following is satisfied:

[0131] In the anti-aging masterbatch, the light stabilizer includes a hindered amine light stabilizer;

[0132] In the anti-aging masterbatch, the antioxidant includes a composite type of hindered phenols and phosphites;

[0133] In the ultraviolet absorbing masterbatch, the ultraviolet absorber includes at least one of a salicylate ultraviolet absorber, a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber, a hindered amine ultraviolet absorber, a substituted acrylonitrile ultraviolet absorber and a triazine ultraviolet absorber.

[0134] In the embodiment of the present application, hindered amine light stabilizers, hindered phenols and phosphite antioxidants are added to the anti-aging masterbatch. After absorbing light energy under aerobic conditions, the hindered amine light stabilizer can be converted into nitroxide free radicals NO·, which can capture the alkyl active free radicals generated in the photo-oxidative degradation of polymer materials and decompose their peroxides. A more preferred solution can add an alkaline low-NOR type light stabilizer. The introduction of alkoxy groups reduces the density of active nitrogen electron clouds and can also directly form nitroxide free radicals NO·, which can avoid the process of traditional hindered amines generating nitroxide free radicals being delayed or blocked by chemical substances, and has a good application effect in a high-concentration pesticide environment (such as sulfur-containing pesticides).

[0135] In the embodiments of the present application, an antioxidant is added to the anti-aging masterbatch, and the antioxidant plays the role of capturing free radicals and decomposing the generated peroxides during the production process or the thermal oxidative decomposition process.

[0136] Furthermore, the synergistic effect of the antioxidant, the hindered amine light stabilizer and the ultraviolet absorber in the embodiment of the present application has better weather resistance than the application of any one or two of them alone. It is also confirmed by experiments that their combination does not inhibit each other. By using the anti-aging masterbatch and the ultraviolet absorption masterbatch in combination, the long-term dustproof shed film can have a service life of 8 years.

[0137] In some embodiments of the present application, the thermal insulation masterbatch includes hydrotalcite masterbatch.

[0138] In the embodiment of the present application, hydrotalcite masterbatch is used as the thermal insulation masterbatch. -1 There is a strong absorption spectrum at 650cm -1 ~1000cm -1 There is a strong vibration absorption spectrum band, which is just in the heat dissipation peak wavelength region of the greenhouse film. Adding hydrotalcite can play a good role in heat preservation. In addition, the addition of hydrotalcite masterbatch can increase the crystal center in the resin, play a role similar to a nucleating agent, increase the number of crystals, reduce the crystal size, thereby reducing the refraction of light and making the film more transparent.

[0139] In some embodiments of the present application, the content of hydrotalcite in the hydrotalcite masterbatch is 20% to 50%.

[0140] In the embodiment of the present application, the hydrotalcite content in the masterbatch is 20% to 50%. The preparation process of the masterbatch at this concentration is the most mature, and there are many commercially available products. The raw materials are simple and easy to obtain, which is relatively economical. In the specific example, the hydrotalcite content in the masterbatch is 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 20 ...

[0141] Further, the hydrotalcite masterbatch includes hydrotalcite masterbatch produced by Kyowa Chemical or hydrotalcite masterbatch produced by Sakai Chemical.

[0142] In some embodiments of the present application, the greenhouse film further includes a coating layer, and the coating layer covers the surface of the inner layer.

[0143] In the present embodiment, the coating layer can be prepared using a commercially available coating liquid. Further, the coating layer has a dry matter content of >0.22 g / m 2 .

[0144] In some embodiments of the present application, the thickness ratio of the outer layer, the core layer and the inner layer is (1-2):(3-8):1, and / or the total thickness of the greenhouse film is 130 μm to 170 μm.

[0145] In the embodiments of the present application, the thickness ratio of the outer layer, the core layer and the inner layer meets the above conditions, which is beneficial to the overall performance of the greenhouse film. Ultraviolet absorbers are added to the outer layer. If the thickness is too low, it will not be conducive to blocking ultraviolet rays and affect the service life of the greenhouse film. If the thickness is too high, the cost will increase due to the high price of ultraviolet absorbers. If the thickness of the inner layer is too low, it will affect the adhesion effect of the coating liquid and the processing equipment will be limited. If the thickness is too high, the cost will increase because the price of polar EMA resin is relatively high. In specific examples, the thickness ratio of the outer layer, the core layer and the inner layer is 1:3:1, 1:4:1, 1:5:1, 1:6:1, 1:7:1, 1:8:1, 2:3:1, 2:4:1, 2:5:1, 2:6:1, 2:7:1, 2:8:1, etc.

[0146] In this embodiment, the total thickness of the greenhouse film is limited to 130μm to 170μm. This thickness is conducive to ensuring the mechanical properties and light transmittance of the greenhouse film. In the specific example, the total thickness of the greenhouse film is limited to 130μm, 131μm, 132μm, 133μm, 134μm, 135μm, 136μm, 137μm, 138μm, 139μm, 140μm, 41μm, 142μm, 143μm, 144μm, 145μm, 146μm, 147μm, 148μm, 149μm, 150μm, etc.

[0147] The second aspect of the embodiment of the present application provides a method for preparing a greenhouse film, comprising the steps of:

[0148] The components of the outer layer, core layer and inner layer are mixed and stirred respectively, and added into a three-layer co-extruder, and the above-mentioned greenhouse film is obtained after melt plasticization blow molding, cooling and shaping, pulling, corona, coating liquid impregnation, drying and folding.

[0149] The method for preparing the greenhouse film of the embodiment of the present application is scientific and reasonable, with stable and reliable quality, and is simple and easy to operate. The greenhouse film prepared in the embodiment of the present application has an outer layer as a dustproof and aging-resistant layer, a core layer as a heat-insulating and aging-resistant layer, and an inner layer as a coating liquid bearing layer. The raw material components and dosages of each layer meet the above conditions, which is conducive to achieving a long-term dustproof function. The multi-layer greenhouse film provided in the embodiment of the present application uses a special structure polymer permanent antistatic agent in the outer layer, and with the material design of the matrix resin, it can be dispersed in the outer film in a special form, and the generated static electricity is conducted and released through ion conduction, which can eliminate the static electricity charge inside and on the surface of the film, and the polymer permanent antistatic agent does not migrate, and is less affected by the humidity of the environment, which is conducive to achieving a long-term dustproof effect.

[0150] In some embodiments of the present application, in the method for preparing greenhouse film, the control parameters include:

[0151] The temperature of the extruder is 150℃~200℃, and the die temperature is 190℃~215℃;

[0152] The drying temperature is 85℃~102℃;

[0153] The blow ratio of blow molding is 1.5 to 2.5.

[0154] In some embodiments of the present application, a method for preparing an aging-resistant masterbatch is provided, comprising the steps of:

[0155] Use a high-speed mixer to mix polyethylene II, light stabilizer and antioxidant at high speed according to proportion, add them into an internal mixer for kneading, and then feed them into a twin-screw extruder through a feeder. After water ring or underwater pelletizing, an aging-resistant masterbatch is obtained.

[0156] In some embodiments of the present application, a method for preparing a UV absorbing masterbatch is provided, comprising the steps of:

[0157] Polyethylene II and ultraviolet absorber are mixed at high speed according to proportion using a high-speed mixer, added into an internal mixer for kneading, and then fed into a twin-screw extruder through a feeder, and pelletized through a water ring or underwater to obtain an ultraviolet absorbent masterbatch.

[0158] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0159] Example 1

[0160]

Shed film

[0161] The greenhouse film is composed of an outer layer, a core layer, an inner layer and a coating layer in sequence. The amount of each layer component is calculated by weight. The specific components of each layer are as follows:

[0162] 1. Outer layer

[0163] Polyethylene I: 60 parts, XP 6056ML from Exxon.

[0164] Polar resin I: 10 parts, ethylene-methacrylic acid copolymer, methacrylic acid content is 18%, Arkema's 18MA02.

[0165] Polar resin II: 10 parts, ethylene-vinyl acetate copolymer, the content of vinyl acetate is 18% Hanwha Total Petrochemical's E180L.

[0166] Dust suppressant: 10 parts, FSTAT2 from Hoda.

[0167] Anti-aging masterbatch: 8 parts.

[0168] UV absorbing masterbatch: 2 parts.

[0169] 2. Core layer

[0170] Polyethylene I: 60 parts, XP 6056ML from Exxon.

[0171] Polar resin II: 20 parts, ethylene-vinyl acetate copolymer, vinyl acetate content is 18%, E180L of Hanwha Total Petrochemical.

[0172] Thermal insulation masterbatch: 5 parts, 36% concentration hydrotalcite masterbatch from Shandong Kuanli.

[0173] Anti-aging masterbatch: 15 parts.

[0174] 3. Inner layer

[0175] Polyethylene I: 70 parts, XP 6056ML from Exxon.

[0176] Polar resin I: 10 parts, ethylene-methacrylic acid copolymer, methacrylic acid content is 18%, Arkema's 18MA02.

[0177] Polar resin II: 15 parts, ethylene-vinyl acetate copolymer, vinyl acetate content is 18%, E180L of Hanwha Total Petrochemical.

[0178] Anti-aging masterbatch: 5 parts.

[0179] 4. Preparation of greenhouse film

[0180] The components of the outer layer, core layer and inner layer are mixed and stirred evenly, added into a three-layer co-extrusion extruder, and melt-plasticized, blown, cooled, shaped, drawn, corona, impregnated with coating liquid, dried, and folded to obtain the finished shed film; the thickness of the prepared product is 150μm; the thickness ratio of the outer layer, core layer and inner layer is 1.5:5:1; the blowing ratio is 2.2. The extruder temperature is 190℃, the die temperature is 210℃, and the oven temperature is 95℃.

[0181] The components and preparation methods of the aging-resistant masterbatch, the ultraviolet absorption masterbatch and the coating layer are as follows:

[0182] (1) Aging-resistant masterbatch:

[0183] The raw material composition of the anti-aging masterbatch is as follows: 55 parts of polyethylene II, 42 parts of light stabilizer, and 3 parts of antioxidant. Among them, polyethylene II uses low-density polyethylene powder with a melt index of 3.5g / 10min; the stabilizer uses Cytec 3529; and the antioxidant uses Changchun Chemical 1010.

[0184] The preparation method of the aging-resistant masterbatch is as follows: 55 parts of polyethylene II, 42 parts of light stabilizer and 3 parts of antioxidant are accurately measured and added into an internal mixer for kneading and plasticization, and then fed into a single-screw extruder granulator through an open mixer, and then hot pelletized and air-cooled and dried to obtain the aging-resistant masterbatch for use.

[0185] The temperature of the internal mixer is 135°C, the plasticizing time is 20 min, and the temperature of each section of the single screw is 140°C to 160°C (including 160°C in zone 1, 160°C in zone 2, and 140°C in zone 3).

[0186] (2) UV absorbing masterbatch:

[0187] The raw material composition of the ultraviolet absorption masterbatch is as follows: 80 parts of polyethylene II and 20 parts of ultraviolet absorber. Among them, polyethylene II uses low-density polyethylene powder with a melt index of 3.5g / 10min; the ultraviolet absorber uses BASF 1577.

[0188] The preparation method of the ultraviolet absorption masterbatch is as follows: 80 parts of polyethylene II and 20 parts of ultraviolet absorber are accurately measured and added into an internal mixer for kneading and plasticization, and then fed into a single-screw extruder granulator through an open mixer, and then hot pelletized and air-cooled and dried to obtain the ultraviolet absorption masterbatch for use.

[0189] The temperature of the internal mixer is 135°C, the plasticizing time is 20 min, and the temperature of each section of the single screw is 140°C to 160°C (including 160°C in zone 1, 160°C in zone 2, and 140°C in zone 3).

[0190] (3) Coating layer:

[0191] The coating layer raw material composition is as follows: 9% coating liquid stock solution and 91% deionized water. The coating liquid stock solution is TG-150, which is manufactured by Takemoto Oil Co., Ltd. of Japan.

[0192] The preparation method of the coating layer is as follows: add the weighed coating liquid stock solution into a stainless steel tank, then add deionized water according to the proportion, stir evenly, let it stand for 20 minutes, and then pump it into the hanging liquid tank for use. The dry matter content of the coating layer is 0.25g / m 2 .

[0193] Example 2-Example 4

[0194] The greenhouse films provided in Examples 2 to 4 are the same as those in Example 1, except that the dosages of the components are changed, as specifically shown in Tables 1 to 3.

[0195] Comparative Example 1-Comparative Example 6

[0196] The greenhouse films provided in Comparative Examples 1 to 6 are the same as those in Example 1, except that the components and dosages are changed, as specifically shown in Tables 1 to 3.

[0197] Among them, the ordinary dust-proof agent added to the outer layer formula of comparative example 5 is a commercially available ordinary dust-proof masterbatch, for example, the brand EFT997 produced by Tianjin Riken Co., Ltd. or the brand BE-10F produced by Jilin Baien Plastic Technology Co., Ltd. The ordinary dust-proof masterbatch used in this comparative example 5 is the brand EFT997 produced by Tianjin Riken Co., Ltd.

[0198] Comparative Example 6 introduces 10 parts by weight of commercially available internal addition type drip defogging masterbatch into the inner layer formula, for example, brand KF-650 and CF-702 produced by Tianjin Riken Co., Ltd. This comparative example uses brand KF-650.

[0199] Table 1 Raw material composition of outer layer

[0200]

[0201] Table 2 Raw material composition of core layer

[0202]

[0203] Table 2 Inner layer raw material composition

[0204]

[0205] Performance Testing

[0206] 1. Detection method:

[0207] 1. Surface resistance:

[0208] (1) External appearance: visual inspection.

[0209] (2) Initial resistance: tested based on GB / T 1410-2006.

[0210] (3) 40℃ water boiling test: Place the sample in a 40℃ water bath, age for 24 hours, take it out, and dry it at room temperature. Finally, measure the surface resistance of the sample according to GB / T 1410-2006.

[0211] (4) 60°C migration test: The sample was placed in a 60°C oven for 8 days, then taken out and the surface resistance of the sample was measured according to GB / T1410-2006.

[0212] (5) Room temperature water flushing test: In a room temperature environment, fix the sample 10 cm away from the bathroom shower, then flush it with tap water for 24 hours and dry it at room temperature. Measure the surface resistance of the sample according to GB / T 1410-2006.

[0213] 2. Water bath test for drip and defogging performance: The drip and defogging performance is tested according to the 4.6 drip performance test regulations in the industry standard "Coated long-lasting drip polyethylene shed film" QB / T4475-2013. The test time for 3-year film is 60 days, 5-year film test time is 90 days, 6-year film test time is 105 days, 7-year film test time is 120 days, and 8-year film test time is 135 days.

[0214] 3. Others:

[0215] (1) Infrared transmittance: tested in accordance with T / CPIA 0015-2019.

[0216] (2) Resistance to ultraviolet radiation dose: Tested in accordance with T / CPIA 0015-2019.

[0217] 2. Test results:

[0218] Table 4 Surface resistance test results of samples provided in the examples and comparative examples

[0219]

[0220] The test results shown in Table 4 show that the surface resistance of the samples provided in Examples 1 to 4 is within 10 11And below, which means that the greenhouse film is more conductive, so that it can effectively leak static electricity and reduce the accumulation of static electricity. In this way, the possibility of static discharge is reduced, avoiding various problems caused by static electricity, such as adsorption of dust, etc.; and it can be stable after various aging, indicating that the overall formula of the outer layer using a polymer permanent antistatic agent has excellent antistatic performance and can have a long-term dust-proof effect. Comparative Examples 1, 3, and 5-6 cannot achieve a good antistatic effect because no or a small amount of polymer permanent antistatic agent is added. Comparative Examples 2 and 4 have appearance problems due to inappropriate resin systems.

[0221] Table 5 Water bath test results of droplet defogging performance of samples provided in the examples and comparative examples

[0222]

[0223] The test results reflected in Table 5 show that the samples provided in Examples 1-4, the introduction of polar resin as a whole, and the greenhouse film prepared by the coating process have a long duration of drip defogging function that can be synchronized with the service life of the greenhouse film. Comparative Examples 1-5 have inappropriate proportions of polar resins, and Comparative Example 6 uses an internally added drip defogging agent, so the drip defogging duration is less than 6-7 years.

[0224] Table 6 Performance test results of samples provided in the examples and comparative examples

[0225]

[0226] The test results reflected in Table 6 show that the infrared transmittance and ultraviolet radiation resistance of the samples provided by Examples 1-4 are all better than those of Comparative Examples 1-6, reflecting that their thermal insulation performance and aging resistance are significantly improved.

[0227] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A greenhouse film, characterized in that: include: an outer layer and an inner layer, and a core layer located between the outer layer and the inner layer; The components of the outer layer include, based on 100 parts by mass: Polyethylene I, 40 to 60 parts, Polar resin I, 10 to 20 parts, Polar resin II, 10 to 20 parts, Dust suppressant, 5 to 15 parts, Anti-aging masterbatch, 5 to 20 parts, UV absorbing masterbatch, 1 to 7 parts; The components of the core layer include, based on 100 parts by mass: Polyethylene I, 40 to 60 parts, Polar resin II, 20 to 40 parts, Insulation masterbatch, 1 to 6 parts, Anti-aging masterbatch, 5 to 20 parts; The components of the inner layer include, based on 100 parts by mass: Polyethylene I, 50 to 70 parts, Polar resin I, 10 to 20 parts, Polar resin II, 10 to 20 parts, Anti-aging masterbatch, 0 to 15 parts; The polar resin I comprises ethylene-methacrylic acid copolymer; The polar resin II includes ethylene-vinyl acetate copolymer; The dust-proof agent comprises a polymer permanent antistatic agent.

2. The greenhouse film according to claim 1, characterized in that: In the ethylene-methacrylic acid copolymer, the content of methacrylic acid is 12% to 29%; And / or, in the ethylene-vinyl acetate copolymer, the content of vinyl acetate is 8% to 18%.

3. The greenhouse film according to claim 1, characterized in that: The melting point of the dust-proof agent is less than 150° C., and / or the dust-proof agent is a polyamide polyether type polymer antistatic agent, and the viscosity thereof is greater than the viscosity of the mixture of the polyethylene I, the polar resin I and the polar resin II.

4. The greenhouse film according to claim 1, characterized in that: The melt index of the polyethylene I is 0.2 g / 10 min to 1.0 g / 10 min.

5. The greenhouse film according to any one of claims 1 to 4, characterized in that: The components of the anti-aging masterbatch include, based on 100 parts by mass: Polyethylene II, 40 to 60 parts, Light stabilizer, 30 to 50 parts, Antioxidant, 0.5 to 5 parts; And / or, based on 100 parts by mass, the components of the ultraviolet absorbing masterbatch include: Polyethylene II, 70 to 90 parts, Ultraviolet absorber, 10 to 30 parts.

6. The greenhouse film according to claim 5, characterized in that: The polyethylene II includes low-density polyethylene, and the melting index of the polyethylene II is ≥2.0g / 10min.

7. The greenhouse film according to claim 5, characterized in that: At least one of the following is met: In the anti-aging masterbatch, the light stabilizer includes a hindered amine light stabilizer; In the anti-aging masterbatch, the antioxidant includes a composite type of hindered phenols and phosphites; In the ultraviolet absorbing masterbatch, the ultraviolet absorber includes at least one of a salicylate ultraviolet absorber, a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber, a hindered amine ultraviolet absorber, a substituted acrylonitrile ultraviolet absorber and a triazine ultraviolet absorber.

8. The greenhouse film according to claim 1, characterized in that: The thermal insulation masterbatch comprises hydrotalcite masterbatch.

9. The greenhouse film according to claim 1, characterized in that: It also includes a coating layer, which covers the surface of the inner layer.

10. The greenhouse film according to any one of claims 1 to 9, characterized in that: The thickness ratio of the outer layer, the core layer and the inner layer is (1-2):(3-8):1, and / or the total thickness of the greenhouse film is 130 μm to 170 μm.

Citation Information

Patent Citations

  • Coating type dimming dustproof high-heat-preservation long-acting dripping fog dissipation greenhouse film and preparation method thereof

    CN112840915A

  • High-heat-resistance permanent antistatic material and preparation method thereof

    CN114230965A

  • Antistatic polypropylene coating material and preparation method thereof

    CN115058155A

  • Antistatic polyethylene composition and product thereof, and preparation method thereof

    CN118652490A